Outcome Comparison Between Obese and Nonobese Patients With Singleton Gestations Following Cerclage Placement [38F]. Issue 1 (May 2017) - Rodriguez, Phillip Andres; Patwardhan, Sanjay; Ebeling, Myla; Sullivan, Scott; Vessa, Blake
Abstract : INTRODUCTION: Cervical cerclage is an established treatment in preventing preterm birth, however, there are little data regarding the effect of obesity on cerclage efficacy. The primary purpose of this study was to identify the effect of obesity on preterm birth prevention in patients undergoing cerclage placement. METHODS: A retrospective cohort study was performed at a single teaching institute and included all singleton pregnancies that underwent McDonald cerclage placement between 2006 and 2014. The study group consisted of patients with a body mass index (BMI) greater than or equal to 30 kg/m 2 and was stratified into obesity classes based on World Health Organization (WHO) criteria. The control group consisted of patients with a BMI less than 30 kg/m 2 . Additional variables included maternal demographics, progesterone use, cerclage indication, and maternal co-morbidities (hypertension, smoking, history of preterm birth and diabetes). RESULTS: 326 deliveries were included. There was a statistically significant latency between non-obese and class III obesity in reaching 30 weeks gestation (70% vs 55%, P = .0477). There was no difference in delivery less than 37 weeks and no difference in neonatal outcomes (Apgar scores, intubation, ICU admission, interventricular hemorrhage). There was a significant increase of chorioamnionitis in class III obesity (47% vs 14%, P < .005). A non-significant increase in the rate of preterm premature rupture of membranes (PPROM) with increasing BMI class was observed. CONCLUSION: In patient's undergoing cerclage placement, class III obesity appears to increase the risk of earlier preterm birth as well as antenatal maternal complications (PPROM and chorioamnionitis) however this had no impact on neonatal outcomes.